Secondary C1q Deficiency in Activated PI3Kδ Syndrome Type 2 - Hong, Ying; Nanthapisal, Sira; Omoyinmi, Ebun; Olbrich, Peter; Neth, Olaf; Speckmann, Carsten; Lucena, Jose Manuel; Gilmour, Kimberly; Worth, Austen; , Genomics England Research Consortium; Klein, Nigel; Eleftheriou, Despina; et al. (Frontiers in Immunology, 2019)
Monogenic forms of vasculitis are rare, but increasingly recognised. Furthermore, genetic immunodeficiency is increasingly associated with inflammatory immune dysregulatory features, including vasculitis. We describe a child of non-consanguineous parents who presented with chronic digital vasculitis from early in life, short stature, facial dysmorphia, immunodeficiency (low serum IgA, high serum IgM), recurrent bacterial infections, lymphoproliferation, absence of detectable serum C1q, and low classical complement pathway activity. We identified a previously reported de novo heterozygous pathogenic splice mutation in PIK3R1 (c.1425+1G>A) resulting in skipping of exon 11 of the p85α subunit of phosphatidylinositol 3-kinase causing activated PI3Kδ syndrome type II (APDS2). This fully explained the phenotype, with the exception of digital vasculitis and C1q deficiency, which has never been described in association with APDS2. No mutations were identified in C1QA, B, or C, their promoter regions, or in any other complement component. Functional studies indicated normal monocytic C1q production and release, suggesting that the observed C1q deficiency was caused by peripheral consumption of C1q. Since C1q deficiency has never been associated with APDS2, we assessed C1q levels in two unrelated patients with genetically confirmed APDS2, and confirmed C1q deficiency in those 2 cases as well. This observation suggests C1q deficiency to be an inherent but previously unrecognized feature of APDS2. We speculate that consumption of C1q is driven by increased apoptotic bodies derived from immune cellular senescence, combined with elevated IgM production (both inherent features of APDS2). Secondary C1q deficiency in APDS2 may further contribute to immunodeficiency, and could also be associated with inflammatory immune dysregulatory phenotypes, such as the digital vasculitis observed in our case.